Fresh produce on the loose: examining the coherence between plastic packaging and food waste policy using the case study of fruit and vegetables in the UK - Sarah Greenwood; Christian Reynolds (Environmental Research: Food Systems)
The UK fresh produce sector (fruit and vegetables) uses 38 kt of plastic consumer packaging per year and is the fifth largest product category for the creation of plastic waste in the UK. One way of addressing this is to sell fresh produce loose, without packaging. This study takes a mixed methods approach of a literature search of historical loose produce trials and a policy coherence analysis of plastic packaging and food waste policy, addressing the research gaps in those areas. The results are used to check progress against UK Plastics Pact (UKPP) targets and alignment with Courtauld 2030 (C2030) and the United Nations Sustainable Development Goal (SDG) 12.3 on food waste. Both methods highlight a tension between food waste and plastics reduction policies at all levels and the literature survey shows there is now a will amongst retailers to overcome this. This incoherence is mitigated using caveats in the plastics policies, such as ‘where shelf-life is unaffected’. There is additional scope to harmonise further by addressing compostables and reduction targets. Supermarkets’ plastics policies are shown to be generally coherent with each other and the pact, but implementation of individual policies between retailers varies considerably. For the removal of consumer packaging from fresh produce to continue, food waste in the supply chain, the amount of transit packaging used, and wider social engagement on packaging and food waste must be considered. The need for better data on packaging usage is highlighted.